Factors associated with the time to cessation of breastfeeding among mothers who have index children aged two to three years in Debre Markos, northwest Ethiopia: a retrospective follow up study - Melkamu Tamir Hunegnaw; Kassahun Alemu Gelaye; Bekri Mohammed Ali (BMC, 2018)
Abstract Background Breastfeeding of children, which needs to continue until two years and beyond, is one of the essential requirements for child survival. However, in Ethiopia there is scarcity of literatures on the duration of breastfeeding. Therefore, the aim of this study was to assess the rate of cessation of breastfeeding among mothers with index children aged 2 to 3 years, northwest Ethiopia. Methods A retrospective follow-up study was conducted at Debre Markos town from March 1, 2014 to March 30, 2016. A total of 500 mother-child pairs were selected using the systematic random sampling method by moving from house to house with an interval of three eligible houses. A structured questionnaire was used to collect data. The Cox regression model was employed to identify the predictors of breastfeeding cessation. Results The proportion of women breastfeeding until 2 years was 13.70 per 1000 person- months. HIV-positive mothers decreased the time of breastfeeding by 3.4 times compared to HIV-negative mothers (AHR = 3.41, 95% CI: 1.96, 5.94). Government employee mothers decreased the time of breastfeeding by 2.8 times compared to housewives (AHR = 2.8, 95% CI: 1.80, 4.40).Better education increased the time of breastfeeding (AHR = 0.45, 95% CI: 0.24, 0.58). Number of children, family income, and place of delivery were the other significant predictors of time to cessation of breastfeeding (p < 0.05). Conclusion In this study, the rate of cessation of breastfeeding was good. HIV negative mothers, government employment, number of children, place of delivery, and family monthly income were significant predictors to the time of breastfeeding cessation. Therefore, family planning and breastfeeding education in health institutions are essential to increase breastfeeding duration.